2016
DOI: 10.1167/iovs.16-19580
|View full text |Cite
|
Sign up to set email alerts
|

Baseline MNREAD Measures for Normally Sighted Subjects From Childhood to Old Age

Abstract: PurposeThe continuous-text reading-acuity test MNREAD is designed to measure the reading performance of people with normal and low vision. This test is used to estimate maximum reading speed (MRS), critical print size (CPS), reading acuity (RA), and the reading accessibility index (ACC). Here we report the age dependence of these measures for normally sighted individuals, providing baseline data for MNREAD testing.MethodsWe analyzed MNREAD data from 645 normally sighted participants ranging in age from 8 to 81… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
65
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 46 publications
10
65
4
4
Order By: Relevance
“…Therefore the typical ACC for normally-sighted young adults is 1.0 (Calabrèse, Cheong, et al, 2016;Calabrèse, Owsley, et al, 2016). ACC decreases in adults aged over 40 at a rate of 0.003 units per year, reaching a suggested value of 0.88 by the age of 81 years (Calabrèse, Cheong, et al, 2016). Average ACC values of 0.76 have been noted in a group of observers aged 55-85 years, and of 0.77 for bilateral pseudophakes (Calabrèse, Owsley, et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore the typical ACC for normally-sighted young adults is 1.0 (Calabrèse, Cheong, et al, 2016;Calabrèse, Owsley, et al, 2016). ACC decreases in adults aged over 40 at a rate of 0.003 units per year, reaching a suggested value of 0.88 by the age of 81 years (Calabrèse, Cheong, et al, 2016). Average ACC values of 0.76 have been noted in a group of observers aged 55-85 years, and of 0.77 for bilateral pseudophakes (Calabrèse, Owsley, et al, 2016).…”
Section: Discussionmentioning
confidence: 91%
“…ACC represents the reading speed of an observer over a range of relevant print sizes based on a normalised reading speed of 200wpm. Therefore the typical ACC for normally-sighted young adults is 1.0 (Calabrèse, Cheong, et al, 2016;Calabrèse, Owsley, et al, 2016). ACC decreases in adults aged over 40 at a rate of 0.003 units per year, reaching a suggested value of 0.88 by the age of 81 years (Calabrèse, Cheong, et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…Reportedly, a smaller CPS value means better reading performance, and it indicates that the patient requires a lower level of magnification to read comfortably [25]. It has been reported that MRS is specific to each individual, usually in accordance with their age [13,26,27], and that RA has a weaker effect on daily life because RA is the smallest font size that the patient is able to read. In the present study, although the MRS increased significantly at 12 months post-surgery, its median value changed by approximately 4% from 343 characters per minute (CPM) to 357 CPM, which is considered to be of poor clinical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Reading aloud rate as a function of age based on the MNread test (each dot is a different study; the darker the dot, the more participants were tested) Source:Calabrèse et al (2016) An alternative to the MNread test is the Radner Reading Charts(Radner, Obermayer, Richter- Mueksch, Willinger, Velikay-Parel, & Eisenwort, 2002), also available for several languages.…”
mentioning
confidence: 99%